PEMANFAATAN METODE HEURISTIK DALAM PENCARIAN MINIMUM SPANNING TREE DENGAN ALGORITMA SEMUT - Alamsyah, Alamsyah (MEKTEK, 2010)
Without a program, computer is just a useless box. In general, the search for the minimum spanning tree canbe divided into two methods: conventional and heuristic methods. Use of heuristic methods that are expectedto complete the minimum spanning tree problem with the search results are more varied and with a shortercalculation time.In the conventional method of logic that is used only by comparing the distance of each node and then findthe shortest distance. However, the weakness of conventional methods on the accuracy of the resultsobtained and the resulting error rate in the calculation. It would not be a problem if the data they need onlya little, by contrast with the number of points that a lot will cause increased levels of calculation errors anddecrease the accuracy.The results showed that the parameters of the number of ants (m) and maximum cycle (NCmax) provided amajor influence on the length of the cable and are consistent with the additional parameters Î±, Î², Ï, Î¶, and Qare used for the optimal solution. For the settlement in the case of graph seerhana who has 8 points with thenumber of ants (m = 15) and the maximum cycle (NCmax = 10) obtained an optimal solution to the cablelength by 149 meters with a time computation 0 ms, the optimal cycle 1 and the optimal solution by 60%.